PERLINDUNGAN HUKUM PENERIMA PINJAMAN TERHADAP PENGGUNAAN DATA PRIBADI OLEH PENYELENGGARA LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI DI INDONESIA - Napitupulu, Samuel Abednego (Universitas Negeri Surabaya, 2019)
The development of technology, especially in the field of Information and Electronics gave birth to a new technology, namely Financial Technology (Fintech). In Fintech there are several types, one of which is lending and borrowing money based on information technology or Peer-to-Peer Lending. In its activities, one of the main things used is Personal Data, especially the personal data of loan recipients. In this case, Peer-to-Peer Lending activities are still relatively new, including the use of personal data in electronic systems, so this needs to be examined in the form of legal protection for the use of personal data of loan recipients by Peer-to-Peer Lending providers. The research method used is normative research with a statutory approach, conceptual approach and legal comparison approach. Data collection techniques use library research to study legal material that is relevant to the topic of the problem. The data analysis technique of this research was qualitative method. The results of this study indicate that there are several principles in regulations in Indonesia that can be the basis for the creation of norms to protect personal data, but the implementation of the principles is considered not optimal, there are other things that have not been specifically regulated, causing uncertainty the law for the owner of the Personal Data especially the Borrower. The results of this study also show that in the legal protection of users, especially the protection of Personal Data, do not yet have regulations at the level of Law only in the level of ministerial regulations, so they do not have good legal certainty (in the case of Ministerial replacement, regulations can change at any time) as well in this study, the legal protection of personal data in Indonesia is considered to be lagging behind other Southeast Asian countries, such as the Philippines. The Philippines has an equivalent regulation of the country's law that specifically regulates Personal Data and because of that Act, an Independent Commission was formed based on the Act that specifically handles all matters concerning the Personal Data of Filipino Citizens. Keywords: Legal Protection, Personal Data, Peer-to-peer lending.